Genome-wide dissection of the genetic factors underlying food quality in boiled and pounded white Guinea yam - Asfaw, A.; Agre, A.P.; Matsumoto, R.; Olatunji, A.A.; Edemodu, A.; Olusola, T.; Odom-Kolombia, O.L.; Adesokan, M.; Alamu, E.O.; Adebola, P.O.; Asiedu, R.; Maziya-Dixon, B. (Wiley, 2024)
BACKGROUND Food quality traits related to the genetics of yam influence the acceptability for its consumption. This study aimed at identifying genetic factors underlying sensory and textural quality attributes of boiled and pounded yam, the two dominant food products from white Guinea yam.